Fish canning wastewater treatment in sequencing batch reactor with activated sludge - Grgas, Dijana (Array, 2020)
The biological performance of flocculent sludge in sequencing batch reactor for the treatment of fish canning wastewater was evaluated in terms of organic matter and nutrient removal by gradual increase of salt concentration in the nitritation-denitritation process. Salinity negatively affected the biological system performance in a way that reduced organic and nutrient removal. The removal efficiency of organic matter and nitrogen showed good performance below 20 g NaCl/L, while phosphate accumulating organisms activity was deteriorated and declined during whole experiment. Nitrogen removal occurred as ammonium oxidation with nitrite accumulation. Nitrite reduction was not affected by salt concentration.